Analisis Semiotika Nilai Dakwah dalam Lagu Jiwa yang Bersedih Karya Ghea Indrawari - Muhammad Rifqi Rosyaddin; Bambang Saiful Ma’arif; Nia Kurniati (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. This research focuses on the da'wah method through song media, especially through a song by Ghea Indrawari entitled "Soul that is Sad". This research aims to understand the da'wah method using song media and identify how songs can be a means for da'wah and spread the teachings of Islam. The method used in this study is qualitative, supported by Roland Barthes' semiotic theory. The data was obtained through the collection of secondary data from the content of the Ghea Indrawari podcast. The results of the study show that da'wah through the medium of songs has been carried out since the time of the Prophet Saw, and songs can be a medium of da'wah if the lyrics contain an invitation to goodness, a reminder of goodness, and do not encourage the listener to stay away from the commands of Allah SWT. The song "Sad Soul" by Ghea Indrawari contains many meanings of goodness in it, such as an invitation to kindness, gratitude, and encouragement for listeners to always love themselves and remember the help from Allah in all difficulties faced. With the existence of song media as a means of da'wah, it is hoped that more and more music artists will create songs that have good values in them, just as the Prophet Saw spread Islam to his people. Abstrak. Penelitian ini berfokus pada metode dakwah melalui media lagu, khususnya melalui lagu karya Ghea Indrawari yang berjudul “Jiwa yang Bersedih”. Penelitian ini bertujuan untuk memahami metode dakwah menggunakan media lagu dan mengidentifikasi bagaimana lagu dapat menjadi sarana untuk dakwah serta menyebarkan ajaran Agama Islam. Metode yang digunakan dalam penelitian ini adalah kualitatif, didukung oleh teori semiotika Roland Barthes. Data diperoleh melalui pengumpulan data sekunder dari konten podcast Ghea Indrawari. Hasil penelitian menunjukkan bahwa dakwah melalui media lagu telah dilakukan sejak zaman Rasulullah Saw, dan lagu dapat menjadi media dakwah jika liriknya mengandung ajakan kepada kebaikan, pengingat dalam kebaikan, dan tidak mendorong pendengarnya untuk menjauhi perintah Allah SWT. Lagu “Jiwa yang Bersedih” karya Ghea Indrawari mengandung banyak makna kebaikan di dalamnya, seperti ajakan kepada kebaikan, rasa syukur, dan dorongan bagi pendengarnya untuk selalu mencintai diri sendiri serta mengingat adanya bantuan dari Allah dalam segala kesulitan yang dihadapi. Dengan adanya media lagu sebagai sarana dakwah, diharapkan semakin banyak seniman musik yang menciptakan lagu-lagu yang memiliki nilai-nilai kebaikan di dalamnya, sebagaimana Rasulullah Saw menyebarkan agama Islam kepada umatnya.